Simulation defect de température sur les performance d'une cellule solaire basé aux pérovskite MAPbCl3 - أمين, محمد; بوبكر, مسعودي; زكرياء, شراد (University of El-Oued, 2022)
"In this note, the effect of heat on the characteristic properties of a solar cell was studied, and to find out the efficiency of the photovoltaic parameters, the structure of the perovskite cell (CH3NH3PbCl3) was modified and various performance parameters such as Jsc, FF, Voc and eta were calculated. The simulation takes place in both dark and bright lighting conditions. The results obtained through the study show that when the temperature increases, the efficiency of the photovoltaic parameters decreases and therefore the temperature negatively affects the photovoltaic parameters only. ""في هذه المذكرة، تمت دراسة تأثير الحرارة على الخصائص المميزة لخلية شمسية، وللتعرف على كفاءة المعلمات الكهروضوئية ، تم تعديل بنية خلية البيروفسكايت (CH3NH3PbCl3) وتم حساب معلمات الأداء المختلفة مثل Jsc و FF و Voc و eta تجري المحاكاة في ظروف الإضاءة المظلمة والمشرقة. النتائج المتحصل عليها من خلال الدراسة تبين أنه عندما تزداد درجة الحرارة ، تنخفض كفاءة المعلمات الكهروضوئية وبالتالي فإن درجة الحرارة تأثر سلبا المعلمات الضوئية فقط. "
مذكرات ماستر تخصص اتصالات
Keywords: solar cell, temperature,characteristics.; الخلية الشمسية، درجة الحرارة، الخصائص المميزة.